TaqMan real-time PCR for detection of pathogenic Leptospira spp. in canine clinical samples - Abdul Rahman, Mohammad Sabri; Khor, Kuan Hua; Bejo, Siti Khairani; Lau, Seng Fong; Mazlan, Mazlina; Roslan, Mohd Azri; Md Ajat, Mohd Mokrish; Mohd Noor, Mohd Akmal (Sciendo, 2023)
Introduction: Canine leptospirosis has always been a differential diagnosis in dogs presenting with clinical signs and blood profiles associated with kidney and/or liver disease. The conventional polymerase chain reaction (PCR) provides diagnoses, but real-time PCR-based tests provide earlier confirmation and determine the severity of infection, especially in the acute stage, allowing early detection for immediate treatment decisions. To our knowledge, real-time PCR has not been routinely adopted for clinical investigation in Malaysia. This study evaluated TaqMan real-time PCR (qPCR) assays diagnosing leptospirosis and compared their applicability to clinical samples from dogs with kidney and/or liver disease against a conventional PCR reference. Material and Methods: The qPCR assays were validated using existing leptospiral isolates. Whole blood and urine samples were analysed using a conventional PCR, LipL32(1) and LipL32(2) qPCRs and a microscopic agglutination test. The sensitivity and specificity of the qPCRs were determined. Results: The LipL32(1) qPCR assay had more diagnostic value than the LipL32(2) qPCR assay. Further evaluation of this assay revealed that it could detect as low as five DNA copies per reaction with high specificity for the tested leptospiral strains. No cross-amplification was observed with other organisms. Analysing the clinical samples, the LipL32(1) qPCR assay had 100.0% sensitivity and >75.0% specificity. Conclusion: The LipL32(1) qPCR assay is sensitive, specific and has the potential to be applied in future studies.